Sosialisasi Ilmu Mitigasi Tsunami Bagi Masyarakat Pesisir dan Dataran Rendah di Pagar Dewa - angky, puspawan; Gunawan, Agustin; FA, A. Sofwan; Razali, Makmun Reza; Bismantolo, Putra; Zuliantoni, Zuliantoni (Dharmakayana, 2025)
Bengkulu City is a region with a high risk of tsunami due to its location adjacent to the Indian Ocean and its position in an active subduction zone. The low level of public knowledge regarding disaster mitigation increases the potential for casualties in the event of a tsunami. This community service activity aimed to enhance the understanding, awareness, and preparedness of residents in Pagar Dewa Village, Selebar District, Bengkulu City, regarding tsunami hazards through mitigation-based education and socialization. The implementation methods included socialization (counseling), interactive discussion and dialogue, presentation of evacuation routes, and information on prevention and emergency response. The results showed a significant increase in public knowledge and preparedness, demonstrated by participants’ ability to recognize early tsunami signs and take appropriate evacuation actions. Residents also showed high enthusiasm and emphasized the importance of ongoing training to maintain mitigation awareness. This activity successfully built synergy between the university, local government, and the community in reducing disaster risks in coastal and lowland areas around Bengkulu City. Therefore, tsunami mitigation education is a strategic step toward creating a disaster-resilient community and strengthening readiness for future natural threats.